High Performance Liquid Chromatographic Method for the Determination of Chlordiazepoxide in Pharmaceutical Preparations Application to content uniformity testing - Nief Rahman Ahmed (College of Pharmacy / Mustansiriyah University, 2018)
A reverse phase high performance liquid chromatographic method (HPLC) has been developed for the determination of  chlordiazepoxide in the pharmaceutical formulations . Separation was achieved using supelco C18 column(25cm x 4.6 mm. 5 µm). The mobile phase (ethanol), adjusted pH to 1.0 with 1N sulfuric acid and pumped at a flow rate of 1.0 ml/min . The peaks  were detected at 310 nm. Linearity was obtained in the concentration range of 0.01- 0.20 mg/ml .The method was statistically validated and RSD was found to be less than 1.5 % indicating high degree of accuracy and precision of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining chlordiazepoxide in pure drug samples, and pharmaceutical dosage forms.